Prediction of Marital Burnout Based on Sexual Health Literacy in Married Women: The Mediating Role of Sexual Satisfaction - Mahsa Najafi; Forough Esrafilian; Parviz Azadfallah (روانشناسی بالینی و شخصیت)
Introduction: Marital burnout is a significant challenge in married life that can adversely affect the quality of relationships and the mental health of couples. Given the rising rates of divorce and marital dissatisfaction, investigating this issue has become increasingly important. This study aims to examine the role of sexual health literacy in predicting marital burnout among married women, with a particular emphasis on the mediating role of sexual satisfaction.Method: This descriptive study employed a correlational research design. The sample comprised 212 married women from Kermanshah city in 2022, selected through convenience sampling. Data were collected using the Pines Marital Burnout Scale (1996), Masoumi et al.’s Sexual Health Literacy Scale (2019), and Hudson et al.’s Sexual Satisfaction Index (1981). Data analysis was performed using SPSS-24 and AMOS-24 software.Results: The findings revealed that sexual health literacy had a positive and significant effect on sexual satisfaction (β = 0.68) and a negative and significant impact on marital burnout (β = -0.85). Additionally, sexual satisfaction had a negative and significant effect on marital burnout (β = -0.45, P < 0.05). Bootstrap test results indicated that sexual health literacy indirectly influenced marital burnout through the mediating role of sexual satisfaction (β = 0.37). Sexual satisfaction served as a mediator between these two variables. The results also demonstrated that the total effect of sexual health literacy on sexual satisfaction was significant (β = 0.64).Discussion and conclusion: This study demonstrated that sexual health literacy, by enhancing sexual satisfaction, contributes to a reduction in marital burnout. Therefore, improving sexual health literacy can serve as an effective strategy to strengthen marital relationships and prevent marital burnout. It is recommended that educational and counseling programs focused on sexual health be designed and implemented for married women to enhance the quality of marital relationships through increased awareness.